Pengaruh Pengalaman Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan di PT. BPR Hayura Artalola - Delvi Kusumah Dewi; Ayu Nike Retnowati; Retno Widya Ningrum (Ma'soem University, 2023)
The problems that occur are fluctuating employee performance achievements, lack of employee work experience and lack of comfort in the physical work environment in the company. This research aims to determine respondents' responses regarding the situation and how much influence work experience variables and the physical work environment have on employee performance at PT. BPR Hayura Artalola and its partial and simultaneous influence. This research uses descriptive and verification methods with a quantitative approach. The population used in this research was 43 employees with a sample of all employees at PT. BPR Hayura Artalola using non-probability sampling techniques, saturated sampling. Based on the results of data distribution, it was found that work experience was in the fairly high category, the physical work environment was in the quite good category and employee performance was in the good category. Based on the results of the determination test, it was found that work experience had an effect on employee performance by 57.4%, physical work environment had an effect on employee performance by 24%. Work Experience and Physical Work Environment simultaneously influence employee performance by 65.4%. The results of partial hypothesis testing show that work experience influences employee performance with a sig. of 0.000 (0.000 < 0.05) and the t-count value is 7.231 > t-table 2.021. The physical work environment influences employee performance with a sig. of 0.001 (0.001 < 0.05) and the t-count value is 3.419 > t-table 2.021. Based on simultaneous hypothesis testing, it shows that work experience and physical work environment influence employee performance with a sig. < 0.05 (0.000 < 0.05) and F-count value > F-table (40.728 > 3.232).